Changing Graph Use in Corporate Annual Reports: A Time‐Series Analysis - BEATTIE, VIVIEN A.; JONES, MICHAEL J. (Contemporary Accounting Research, 2000)
Graphs in corporate annual reports form part of a powerfully designed annual report package that offers considerable potential for “impression management.” The primary purpose of this paper is to determine whether graph use depends on corporate performance. Time‐series analysis, not previously used in the financial graphs literature, allows discretionary changes in graph use by companies to be identified and related to changes in individual companies' corporate performance over time. Based on the prior financial graphs and accounting choice literature, we develop two hypotheses that relate changes in graph use to changes in corporate performance. These hypotheses focus on the aggregate and individual company levels. We base our analysis on the corporate annual reports of 137 top UK companies that were in continued existence during the five‐year period from 1988 to 1992. At both the aggregate and individual company levels, we find the decision to use key financial variable (KFV) graphs, the primary graphical choice, to be associated positively with corporate performance measures. This finding is consistent with the manipulation hypothesis ‐ that is, that financial graphs in corporate annual reports are used to “manage” favorably the reader's impression of company performance, and hence that there is a reporting bias.